2014
DOI: 10.13102/sociobiology.v59i2.602
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pollen on the Development of Africanized Bee Colonies (Hymenoptera: Apidae)

Abstract: This study aimed to assess the importance of quality and quantity of pollen on the development of colonies in different seasons. The field experiment was conducted at the Apiary of the Department of Entomology and Acarology of Luiz de Queiroz College of Agriculture, using five beehives of A. mellifera. In order to characterize the quality of pollen, researchers considered measures of total dry mass (g) and the physical-chemical and pollen composition of pollen load and bee bread samples. The development of hiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Several factors generate stress during bees ontogeny, such as feeding type (Modro et al, 2012), homeothermal control (Domingos & Gonçalves, 2014), management practices (Lima et al, 2016), and the use of pesticides (Nunes et al, 2015;Prado-Silva et al, 2018). Modro et al (2012) showed that in summer, when temperatures are higher, individuals showed high FA levels when compared to other periods of the year. This shows deviations in the symmetry of individuals with bilateral symmetry, and FA may reflect the development of instability caused by stress due to high temperatures.…”
Section: Figmentioning
confidence: 99%
“…Several factors generate stress during bees ontogeny, such as feeding type (Modro et al, 2012), homeothermal control (Domingos & Gonçalves, 2014), management practices (Lima et al, 2016), and the use of pesticides (Nunes et al, 2015;Prado-Silva et al, 2018). Modro et al (2012) showed that in summer, when temperatures are higher, individuals showed high FA levels when compared to other periods of the year. This shows deviations in the symmetry of individuals with bilateral symmetry, and FA may reflect the development of instability caused by stress due to high temperatures.…”
Section: Figmentioning
confidence: 99%